Pengaruh Store Atmosphere dan Teman Berbelanja Terhadap Keputusan Pembelian Impulsif Pada Konsumen Fashion (Studi Kasus Pada Distro Inspired27 Malang) - Umang Lukito, Kharishmasalam Phasa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The competiton of indie clothing business at Malang is flourishing. So many company that flourish make the competition getting tougher so turn the company to show their exellence and better capability with many marketing strategies, one of those is create the store environment that is comfortable and pleasant for visitors. Environment can be divide into physic environment that is store atmosphere and social environment that is shopping friend. This research has a purpose to knowing and analyze the store atmosphere and shopping friend to impulse buying decision of garment consumer at Inspired27 store Malang, either simultaneously or partially and to find wich variable who has the dominant influence. This research type is explanatory research wich explain about casual relation between variables by hypothesis test. This research use 100 respondents of Inspired27 consumer as sample with purposive sampling tech. Tech that used to collect the data is questionnaires, literature, and browsing the internet. Test equipment used to test the research instruments such as validity, reliability, and classical assumption. Furthermore, hypothesis testing was performed using the F test and T test. From the analysis of data using multiple linear regression, which can be obtained beta coefficient indicates the dominant influence variables. From the results of hypothesis testing, it can be concluded that the variable store atmosphere and shopping friends simultaneously have a significant influence on the impulse buying decision of Inspired27 Malang consumer. Variable store atmosphere and shopping friend partially have a significant on the impulse buying decision of Inspired27 Malang consumer. The variable that have dominant influence on the impulse buying decision of Inspired27 Malang consumer is variable store atmosphere. Key words: store atmosphere, shopping friend, impulse buying decision